2021
DOI: 10.1016/j.ajogmf.2020.100293
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of obstetrics and gynecology articles with highest relative citation ratios, 1980 to 2019

Abstract: BACKGROUND:The Relative Citation Ratio is a novel bibliometric tool that quantifies the impact of research articles. The objectives of this study were to identify the 100 obstetrics and gynecology articles with the highest relative citation ratios, evaluate how characteristics of these articles changed over time, and compare characteristics of these articles with topcited obstetrics and gynecology articles. OBJECTIVE: We undertook a cross-sectional bibliometric study to examine the 100 obstetrics and gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 155 publications
1
9
0
Order By: Relevance
“…It is interesting to note that 76 articles are common to the two lists involved in this study, a number higher than that found for another medical discipline in a similar study, 61/100 [ 46 ]. Comparison of the 24 that were not on both lists reveals noteworthy differences in the years of publication ( Table 6 ): a median of 2004 for the top-cited group, 2009 being the most recent year, and a median of 2014 for the top RCRs, 18 of them in the period 2011–2019.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It is interesting to note that 76 articles are common to the two lists involved in this study, a number higher than that found for another medical discipline in a similar study, 61/100 [ 46 ]. Comparison of the 24 that were not on both lists reveals noteworthy differences in the years of publication ( Table 6 ): a median of 2004 for the top-cited group, 2009 being the most recent year, and a median of 2014 for the top RCRs, 18 of them in the period 2011–2019.…”
Section: Discussionmentioning
confidence: 57%
“…Although the application of the RCR system is relatively new, and direct comparisons among fields are still developing, the expectations for RCR in bibliometric analysis are great and growing, given its documented usefulness [ 38 ]. The RCR was originally designed to assess the scientific impact of NIH-funded research; but it was soon adopted for bibliometric analyses beyond this intended purpose, for instance, to measure the research productivity of scientists or clinicians [ 41 , 42 , 43 , 44 ], to evaluate the characteristics of clinical trials [ 45 ], or to evaluate the most influential articles [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…These types of analyses provide a critical evaluation of available literature and serve as a measure of academic production by researchers. There have been bibliometric studies in other specialties identifying important contributions to their specific fields, including anesthesia, 5 critical care medicine, 6,7 obstetrics and gynecology, 8,9 orthopedic surgery, 10,11 radiology, 12,13 plastic surgery, 14,15 general surgery, 16,17 and dermatology. 18,19 These articles focus on citation counts as a possible way of measuring the influence and importance—“impact” in the parlance of bibliometric analysis—of specific articles on their fields of study.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers across different disciplines have applied various methods to generate these lists of influential papers. Some lists are entirely bibliometric analyses of citations, [1][2][3][4][5][6][7][8][9] some are built on expert consensus, 10,11 and others combine these two approaches. [12][13][14] As these publications become increasingly available in other fields, we aimed to fill this gap in laryngology.…”
Section: Introductionmentioning
confidence: 99%